KARKAS, LEMAK ABDOMINAL DAN ORGAN AKSESORIS AYAM BROILER PADA PENAMBAHAN FITOBIOTIK JAHE MERAH (Zingiber officinale var Rubrum) DAN GULA AREN DALAM RANSUM (Carcas, abdominal fat and accessory organs of broiler chickens on the addition of phytobiotics..) - Lilis Ambarwati; Nurqholis Amir; Muhlan Muhlan; Sulkiana Sulkiana (Universitas Nusa Cendana, 2023)
The quality of livestock products is currently a priority for poultry sector, especially broiler breeders. The purpose of this study was to evaluate the addition of red ginger powder and palm sugar on the quality of meat (slaughter weight, carcass weight, and abdominal fat) and accessory organs (liver, pancreas, and spleen) of broiler chickens. This research method used an experimental method with a Completely Randomized Design (CRD) pattern consisting of four treatments and five replications. The tools and materials used included 40 units of metabolism cages measuring 30 x 40 x 40 cm, feeder and drinkers, thermohygrometers, scales, 100 DOC with initial weight around 44 g. The research diets consisted of P0 = diets (control), P1 = diets + 1.25% SJM + 6% palm sugar, P2 = diets + 1.5% SJM + 6% palm sugar and P3 = diets + 1 .75% SJM + 6% palm sugar. The results based on analysis of variance showed that the addition of red ginger powder had a very significant effect (P<0.01) on slaughter weight and carcass weight, had a significant effect (P<0.05) on lymph weight but had no significant effect (P>0.05 ) on the weight of liver, pancreas and abdominal fat of broiler chickens. The addition of 1.75% red ginger powder obtained the best slaughter weight and carcass weight, while the P0 treatment (control diets) produced the highest lymph weight. The conclusion from the study was that the addition of red ginger powder phytobiotics at a dose of 1.75% was able to produce the best quality with a slaughter weight of 1,976.40 g and carcass weight of 1,389.4 g, but had no effect on the accessory organs of broiler chickens.